Neither friend nor foe: ethnic segregation in school social networks - Bracegirdle, C; Jonsson, JO; Spiegler, O (SAGE Publications, 2023)
High levels of ethnic segregation have been widely observed in school friendship networks, whereas the degree to which school bullying networks are divided along ethnic lines remains uncertain. Using data from 981 students (53% girls, 47% boys; 11–14 years of age) in British schools, we sought to visualize, quantify, and compare the degree of ethnic segregation in friendship and bullying networks. Our findings contradict the common belief that ethnic segregation in friendship networks fosters interethnic conflict; instead, we identified similarly high levels of ethnic segregation in both friendship and bullying networks. Students may therefore simultaneously avoid positive and negative interethnic relationships. The findings indicate that positive and negative networks should both be considered to provide a comprehensive assessment of interethnic relations in the school environment.